MeCP2: Making sense of missense in Rett syndrome - Banerjee, Abhishek (Nature Publishing Group, 2013)
Fine scale genomic regulation is critical for maintaining genomic integrity and is often disrupted in neurodevelopmental disorders. An intriguing new study reveals the intricate biochemical complexity of de novo post-translational modifications of MeCP2, including activity-dependent protein-protein interactions that 'bridge' the nuclear receptor co-repressor (NCoR) complex to chromatin and lead to alterations in gene expression that characterize Rett syndrome.